When It's Only Me: The Experience of an Only Child Caring for an Elderly Mother While Working - Rostina Rostina (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This reflective autoethnographic study explores the lived experience of being an only child caring for an elderly mother with Parkinson's disease while working as a full-time lecturer. The research aims to understand how this dual role affects the caregiver's mental health, work productivity, and relationship with the mother. Using a reflective autoethnographic approach based on Ellis, data were collected through three techniques: autobiographical narratives and memos, analysis of personal artifacts (work schedules, medical records, photographs), and an integrated self-interview. Thematic-reflective analysis revealed three main themes. First, structural loneliness describes the profound isolation resulting from having no sibling to share physical, emotional, and decisional responsibilities, which informal support cannot easily remedy. Second, stealth strategies at work refer to hidden tactics such as leaving early without disclosure, using breaks to check on the mother, and concealing caregiving struggles to avoid being perceived as less committed or losing professional opportunities. Third, fought for bonds shows that despite exhaustion and initial frustration, the caregiver’s relationship with her mother deepened through daily effort, patience, and reframing caregiving as meaningful devotion, a process aligned with filial maturity. The findings highlight the unique pressures faced by only-child working caregivers, including invisible productivity loss and the inadequacy of general social support. Practical implications for employers, social workers, and policymakers are discussed. This study contributes a rich first-person account to the underexplored area of only-child caregiving and offers recommendations for workplace cultural change, targeted support groups, and subsidized respite services.